EVALUASI DATABASE SISTEM INFORMASI ALUMNI UNIVERSITAS MUHAMMADIYAH BENGKULU - Yetman Erwadi; Ema Utami; Hanif Al Fatta (Informasi Interaktif, 2017)
Database is an important part of information system, one of the role of database system that is as source of information for information system. Information system alumni of Muhammadiyah University of Bengkulu is a web-based application that uses MySQL as its database system. Evaluation is done to identify the errors that exist in the database SIAUMB, after the evaluation on the database there are some errors in the database SIAUMB, including errors in the relation, field, key, constraint, record, query, adding data (insert), change data (update) and deletion of data (delete). Future databases can produce an alumni information system capable of providing exploratory information quickly, easily and accurately and able to assist the parties concerned in making management decisions alumni Muhammadiyah University of Bengkulu. Then can be done new database design with reference to result of evaluation which have been done. After that, data quality testing on aspects of accuracy and non-duplicate aspects, testing is done by executing query, each query that executed will generate record and result column then compared between new database with old database before evaluation. Keywords : Database, Alumnus, Evaluation